(untitled) (Journal of the College of Basic Education, 2022)
The goal of this paper is to give an account of the relationship between pragmatics and stylistics which has led to the birth of pragmastylistics or pragmatic stylistics wherein various pragmatic theories are exploited in interpreting literary discourse. Among these theories are the speech act theory, the cooperative principle and conversational implicature theory, in addition to politeness theory. Hence, to form a vivid picture about this newly born field of study, it seems necessary to account for the narrative structure and the corresponding method of analysis. Key words: pragmatics, stylistics, pragmastylistics, narrative structure Pragmatics, Stylistics, and Pragmastylistics Leech (1983: 5) states that meaning is "derived not from the formal properties of words and constructions, but from the way in which utterances are used and how they relate to the context in which they are uttered". Investigating such a kind of relationship is the concern of pragmatics which is, according to Leech (ibid.), a theory of appropriateness. Following Levinson (1983: 5), pragmatics is not directly interested in language, but in what people do with language, its uses, and users. Thus, the simplest definition of pragmatics is that it is "the study of language use" (ibid.). Speakers try by language to change either the world (e.g., by getting another person to do something) or the state of mind or knowledge of others (for instance, by telling them something new). Pragmatics, as such, investigates what language users mean, what they do and how they do it in real situations.